W poszukiwaniu źródeł intensyfikujących znaczeń wyrazów z gniazda morfologicznego grzmieć - Wąsińska, Kinga (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The article presents the word family of the verb grzmieć (to thunder) from the beginning of the Polish language to the 20th century. The research material includes 90 derivatives that have been characterized in terms of word formation and meaning within three values: SOUND, FORCE, and INTENSITY. The synchronic linguistics method of word-formation adapted to historical material allowed for including in the analysis words such as pogrom, zgromić, gromot which lost their formal and semantic connection with the Proto-Slavic root they were based on. The analysis proved that the semantic value of the base and its morphological features influence the development of subsequent meanings of words belonging to the word family. The meaning of intensity especially seen in words such as ogromny, ogromnie, ogromniasty is a kind of exponent of the value inherent in their root and is present in many other words derived from the same Proto-Slavic root.